2013
DOI: 10.1167/13.7.20
|View full text |Cite
|
Sign up to set email alerts
|

Memory color of natural familiar objects: Effects of surface texture and 3-D shape

Abstract: Natural objects typically possess characteristic contours, chromatic surface textures, and three-dimensional shapes. These diagnostic features aid object recognition, as does memory color, the color most associated in memory with a particular object. Here we aim to determine whether polychromatic surface texture, 3-D shape, and contour diagnosticity improve memory color for familiar objects, separately and in combination. We use solid three-dimensional familiar objects rendered with their natural texture, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 50 publications
1
41
0
6
Order By: Relevance
“…In subsequent fMRI studies with neurologically normal participants, Goodale (2007, 2011) have shown that 3-D shape properties, which determine object identity, are processed in a different brain region from material properties. Behavioral reports support these findings (Cant, Large, McCall, & Goodale, 2008), although there is clear evidence of an interaction: Material properties influence the perception of 3-D shape (Fleming et al, 2004;Ho et al, 2008;Fleming, Holtmann-Rice, & Buelthoff, 2011;Wijntjes, Doerschner, Kucukoglu, & Pont, 2012) and vice versa (Bloj et al, 1999;Boyaci et al, 2003;VanGorp et al, 2007;Ho et al, 2008;Olkonnen & Brainard, 2011;Vurro et al, 2013).…”
Section: Materials Categorization Is Not Merely Derived From High-levementioning
confidence: 97%
“…In subsequent fMRI studies with neurologically normal participants, Goodale (2007, 2011) have shown that 3-D shape properties, which determine object identity, are processed in a different brain region from material properties. Behavioral reports support these findings (Cant, Large, McCall, & Goodale, 2008), although there is clear evidence of an interaction: Material properties influence the perception of 3-D shape (Fleming et al, 2004;Ho et al, 2008;Fleming, Holtmann-Rice, & Buelthoff, 2011;Wijntjes, Doerschner, Kucukoglu, & Pont, 2012) and vice versa (Bloj et al, 1999;Boyaci et al, 2003;VanGorp et al, 2007;Ho et al, 2008;Olkonnen & Brainard, 2011;Vurro et al, 2013).…”
Section: Materials Categorization Is Not Merely Derived From High-levementioning
confidence: 97%
“…Smet, Ryckaert, Pointer, Deconinck and Hanselaer [4], while investigating color appearance tolerances for familiar objects, reported similar increases in saturation for memory colors and shifts towards the dominant hue for most familiar objects. Vurro, Ling and Hurlbert [5] also found hue shifts in memory colors of natural objects, but these were not systematically towards the dominant hue of the object. They also found that hue shifts were reduced by increasing the naturalness of the stimuli.…”
Section: Introductionmentioning
confidence: 92%
“…In a more recent and sophisticated study [12] that incorporates the polychromaticity of natural objects participants adjusted only the mean hue of 3-dimensional objects that represented fruits and vegetables to settings that were "redder" and "bluer" than the measured values of the unseen exemplars. A common element between this study and other recent ones [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…They indicate that variations in Chroma and Hue for blue and yellow colors were larger than those for red and green ones and not in the same direction. They also report finding larger shifts for the condition with complex background.In a more recent and sophisticated study [12] that incorporates the polychromaticity of natural objects participants adjusted only the mean hue of 3-dimensional objects that represented fruits and vegetables to settings that were "redder" and "bluer" than the measured values of the unseen exemplars. A common element between this study and other recent ones [e.g.…”
mentioning
confidence: 99%